Evidence for a genetic basis in functional trait tradeoffs with microbial growth rate but not growth yield. (September 2022) - Morrison, Eric W.; Whitney, Shana A.; Geyer, Kevin M.; Sevigny, Joseph L.; Grandy, A. Stuart; Thomas, W. Kelley; DeAngelis, Kristen M.; Frey, Serita D.
Abstract: Tradeoffs in microbial functional traits have been a focus of recently described ecological frameworks and of mathematical models of microbial community functioning. Tradeoffs in key traits such as growth rate, growth yield, resource acquisition, and stress tolerance may have either a genetic basis or a physiological basis, and the type of tradeoff can inform how traits are modeled and measured. Here we provide evidence that growth rate/decomposition and growth rate/stress tolerance tradeoffs have a primarily genetic basis in a phylogenetically diverse suite of ten leaf litter-inhabiting fungi. In contrast, growth yield tradeoffs with functional traits are more likely to have a physiological basis. Consideration of the type of tradeoff, genetic or physiological, should help to inform efforts to model microbial contributions to ecosystem processes, especially when considering different scales. Consideration of physiological tradeoffs may be important for understanding short-term variability (e.g., pulse events) and fine spatial scales, whereas genetic tradeoffs are likely to be useful for understanding regional- to continental-scale and medium- to long-term contributions of microbes to ecosystem processes. Highlights: Growth rate and carbon use efficiency (CUE) of ten fungi were measured in culture. Decomposition enzymes and stress tolerance were assessed by comparative genomics. Traits were compared to identify genetic versus physiological tradeoffs. Growth rate tradeoffs displayed a genetic basis. Carbon use efficiency was highly plastic.